ROUTLEDGE ATLAS OF JEWISH HISTORY. - Gilbert, Martin, 1936-2015. ([S.l.])
1 online resource.
Keywords: This 9th edition of Martin Gilbert's Atlas of Jewish History spans over four thousand years of history in 196 maps, starting with the worldwide migration of the Jews from ancient Mesopotamia and coming up into the first decades of the twenty-first century. It presents a vivid picture of a fascinating people and the trials and tribulations which have haunted the Jewish story, as well as Jewish achievements. The themes covered include: Prejudice and Violence - from the destruction of Jewish independence between 722 and 586 BC to the flight from German persecution in the 1930s. Also covers the incidence of anti-Semitic attacks in the Americas and Europe. Migrations and Movements - from ancient dispersals from the promised land, to new maps on the ingathering of exiles from Arab and Muslim lands from 1948, and from the break-up of the Soviet Union in 1992. Society, Trade and Culture - from Jewish trade routes between 800 and 900, the geography of the Jews of China, of India, to communal life in the ghettoes and the situation of world Jewry in the opening years of the twenty-first century. Politics, Government and War - from the Court Jews of the fifteenth century to the founding and growth of the modern State of Israel. This new edition now includes an additional 39 of Martin Gilbert's maps, across the whole range of Jewish history, originally published across a range of publications, now gathered in this one volume for the first time. Over 50 years on from its first publication, this book is still an indispensable guide to Jewish history.